A longer period of epididymal sperm interaction with extender components during cryopreservation improves sperm quality, decreases the size of sperm distal cytoplasmic droplets, and changes the number of nanoparticles in the extender - de Almeida, Maria Alice; Haupenthal, Laura Gabrielli; Silva, Amanda Nespolo; Schneider, Gabriela Melendes; Rosa, Paola Maria da Silva; de Andrade, André Furugen César; Silva, Luciano Andrade; Meirelles, Flávio Vieira; da Silveira, Juliano Coelho; Perecin, Felipe; Alves, Maíra Bianchi Rodrigues [UNESP] (Elsevier, 2024)
While cryopreservation of cauda epididymal sperm (SpCau) allows the preservation of post-mortem bulls’ gametes, the process triggers sperm damage. Although improving post-thaw sperm quality, using egg yolk extenders (EY) raises biosafety concerns which forces the use of EY-free extenders (EYFE). Since EYFE are less efficient in preserving post-thaw sperm quality, a strategy for ejaculated sperm (SpEj) frozen with EYFE is to add an Equilibrium Time (ET) step period to the cryopreservation process. However, the ET effect on the quality of SpCau cryopreserved in EYFE remains unknown. Distinct from SpEJ, SpCau physiologically displays cytoplasmic droplets (CDs) in the flagellum that may benefit cell exchange during ET. We hypothesized that using ET in SpCau cryopreserved with EYFE impacts sperm morphofunctional features, CD area, and in vitro fertility ability. Extender nanoparticles were also assessed. Following collection from the cauda epididymis of six Nellore bulls by retrograde flow, SpCau were cryopreserved in EYFE BoviFree® (Minitube, Germany) using three ET protocols: ET0 (no-ET); ET2.5 (2.5 h-ET); and ET5 (5 h-ET). SpCau from ET2.5 and ET5 showed a higher (P ≤ 0.05) percentage of motility and integrity of plasma and acrosome membranes and a smaller (P ≤ 0.05) distal CD area. There are no differences in sperm abnormalities, oxidative stress, capacitation-like events, and in vitro fertility ability. However, a better sperm recovery was found after Percoll® selection for ET2.5 and ET5. Interestingly, the number of nanoparticles in the extender decreased in post-thawed samples. In conclusion, an ET of 2.5 or 5 h is required for an efficient SpCau cryopreservation using an EYFE.
Keywords: Blastocyst; Embryo development; Extracellular vesicles; In vitro fertilization; Protoplasmic droplets